Profil Penggunaan Obat Infeksi Saluran Pernapasan Akut (ISPA) Pediatri Rawat Jalan di RS Muhammadiyah Selogiri - Wijayanti, Fitri; Endrawati, Susi; Wahyuningsih, Sri Saptuti (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Acute Respiratory Infection (ARI) is a respiratory tract infection that can last up to 14 days. Common complaints include fever, sneezing, coughing, sore throat, influenza, headache, body weakness and joint pain. The aim of the research was to determine the profile of outpatient pediatric ARI drug use at the Muhammadiyah Selogiri Hospital. This type of non-experimental research is analyzed descriptively, non-analytically, with data collection carried out retrospectively on patient drug prescription medical record data for October – December 2021 which is presented in the form of tables, diagrams or graphs and percentages are calculated. The data was studied using standard guidelines for managing drug selection and rules for using ARI drugs according to WHO: Model Formulary for Children 2010 and the Indonesian Ministry of Health: Pharmaceutical Care for Respiratory Tract Infections 2005. The results of the study showed that the average use of pediatric ARI therapy drugs for antibiotics was the highest. The penicillin supplement used is amoxicillin 59.37%. Supportive therapy with symptomatic analgesic drugs - antipyretics 79.07%, gastrointestinal drugs 4.65%, respiratory tract drugs 35.04%, corticosteroid drugs 37.21% and antihistamines 24.03%. Conclusion: The use of outpatient pediatric ARI drugs at the Muhammadiyah Selogiri Wonogiri Hospital meets the standard management guidelines from WHO: Model formulary for children 2010 and the Indonesian Ministry of Health: Pharmaceutical Care for Respiratory Tract Infections 2005.